2022
DOI: 10.21203/rs.3.rs-1899377/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viruses of a key coral symbiont exhibit temperature-driven productivity across a reefscape

Abstract: One way viruses can affect coral health is by infecting their symbiotic dinoflagellate partners (Symbiodiniaceae). Yet, viral dynamics in coral colonies exposed to environmental stress have not been studied at the reef scale, particularly within individual viral lineages. We sequenced the viral major capsid protein (mcp) gene of positive-sense single-stranded RNA viruses known to infect symbiotic dinoflagellates (‘dinoRNAVs’) to analyze their dynamics in the reef-building coral, Porites lobata. We repeatedly s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…Targeted gene sequencing is increasingly being applied to explore spatiotemporal patterns of viral diversity (Adriaenssens & Cowan, 2014;Finke & Suttle, 2019;Frantzen & Holo, 2019;Gustavsen & Suttle, 2021;Howe-Kerr et al, 2022;Y. Li et al, 2018;Montalvo-Proaño et al, 2017;Prodinger et al, 2020;Short et al, 2010;Tong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Targeted gene sequencing is increasingly being applied to explore spatiotemporal patterns of viral diversity (Adriaenssens & Cowan, 2014;Finke & Suttle, 2019;Frantzen & Holo, 2019;Gustavsen & Suttle, 2021;Howe-Kerr et al, 2022;Y. Li et al, 2018;Montalvo-Proaño et al, 2017;Prodinger et al, 2020;Short et al, 2010;Tong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Dinoflagellate-infecting RNA viruses (dinoRNAVs) are positive-sense, single-stranded RNA viruses hypothesized to infect the dinoflagellate symbionts (Family Symbiodiniaceae) that live in the tissues of reef-building stony corals (Correa et al, 2013;Veglia et al, 2022). Although dinoRNAVs can be prevalent in coral colonies Howe-Kerr et al, 2022;Montalvo-Proaño et al, 2017;Veglia et al, 2022), it is unclear how dinoRNAVs (or Symbiodiniaceae infected by dinoRNAVs) are transmitted among colonies. Recent work has shown that corallivorous (coral-eating) fishes disperse 100s of millions of live Symbiodiniaceae cells across reefscapes in their feces each day (Grupstra et al, 2021).…”
Section: Rna Virus Study Descriptionmentioning
confidence: 99%
See 3 more Smart Citations